Memilih Pasangan yang Sekufu dalam Ormas Keagamaan Perspektif Istihsᾱn - Mukhlisin; Abdul Qodir Zaelani; Relit Nur Edi (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
The concept of kafā’ah (compatibility) in selecting a life partner is one of the fundamental principles in Islamic law, encompassing parity in aspects of religion, social status, economy, and others. In the context of religious organizations, kafā’ah has a more specific dimension, namely equality in terms of beliefs, commitment, and involvement in a particular religious organization. Religious organizations often serve as a medium for shaping an individual's religious identity, making it important to choose a partner from the same organizational background as a factor for maintaining harmony and alignment in family life.In modern times, numerous religious organizations are followed by Muslims. The diversity of these religious organizations affects practices of worship, views on local traditions, and even involvement in social and political issues. Thus, the research problem formulated by the author is: How does choosing a partner with the same religious organization affiliation impact family harmony, and what is the perspective of istihsān regarding marriage between individuals of the same religious organization? The author employs a qualitative research method through a case study approach to produce descriptive and analytical data. The research also uses a normative and sociological approach with a descriptive method. Data collection techniques include interviews, observations, and documentation.Based on field findings, the conclusion of this research is that choosing a partner from the same religious organization does impact family harmony. The harmony within a marriage between partners from the same religious organization can be observed through several indicators: First, there is a balance of rights between husband and wife. Second, there is cooperation in raising and educating children. Third, there is positive interaction with the extended family and society. Fourth, there is mutual support in enhancing spirituality. From the perspective of istihsān, choosing a partner from the same religious organization is preferable for practical application. Istihsān, as a method of istinbāth (derivation of legal rulings), is capable of aligning Islamic law with contemporary issues by selecting the most beneficial option among the good ones. In general principles, the religious criterion in the concept of kafā’ah focuses on a person’s piety and character. However, due to differences in views on piety and character between religious organizations, from the perspective of istihsān, selecting a partner from the same religious organization is prioritized as it is considered more beneficial.